Dermoscopic Features of Melanomas in Organ Transplant Recipients - Sam Polesie; Martin Gillstedt; Oscar Zaar; Amra Osmancevic; John Paoli (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)